Isotropic to distortional hardening transition in metal plasticity. (15th March 2015) - Manopulo, Niko; Barlat, Frédéric; Hora, Pavel
Abstract: The present paper aims to discuss the transition from isotropic to distortional hardening behavior of metallic materials, based on the Homogeneous Anisotropic Hardening (HAH) model. Furthermore, the effect of yield locus distortion on the evolution of the strain increment, under the assumption of associated flow, is theoretically discussed and exemplified. Special cases, such as coaxial and orthogonal stress states, are analyzed to provide better insight into the model. Particular emphasis is put on the monotonic loading case, which is compared to isotropic hardening. Finally, the evolution equations of the state variables are examined and their properties are discussed.